JAZZ BAND IN OCCUPIED ISTANBUL: CULTURAL MEANINGS OF EARLY JAZZ IN THE LIGHT OF CONTEMPORARY SOURCES - Soyturk, Enes Malik; Ayas, Onur Gunes (BURHAN CAGLAR, 2025)
Jazz entered T & uuml;rkiye during the occupation of Istanbul through music ensembles known as jazz band (cazbant). While historical accounts of early jazz in T & uuml;rkiye often treat the 1920s as a unified period, occupied Istanbul presents a distinct historical, social, and cultural context for the reception of jazz compared to the early Republican years. By focusing on cazbant in occupied Istanbul, this study examines how cazbant was interpreted through firsthand accounts. Although some studies highlight the significance of this period, they generally use sources from the Republican period. This situation can sometimes lead to chronological confusion that overlooks the difference in historical contexts. Arguing that the various meanings of jazz are not intrinsic to this musical genre but are shaped by its historical and social context, this study adopts a semiotic approach to explore the system of representation through which jazz in occupied Istanbul was interpreted. The article focuses on the period from 1919 to October 1923, when the occupation officially ended and political authority was restored. The sources include newspaper and magazine articles, advertisements, and fictional and non-fictional works based on firsthand accounts of jazz culture during the occupation years.
Keywords: Ottoman Music History; Ottoman Urban History; Early Jazz; Cazbant; Occupied Istanbul; History